Age-related environmental gradients influence invertebrate distribution in the Prince Charles Mountains, East Antarctica. Issue 12 (December 2016) - Czechowski, Paul; White, Duanne; Clarke, Laurence; McKay, Alan; Cooper, Alan; Stevens, Mark I.
Abstract : The potential impact of environmental change on terrestrial Antarctic ecosystems can be explored by inspecting biodiversity patterns across large-scale gradients. Unfortunately, morphology-based surveys of Antarctic invertebrates are time-consuming and limited by the cryptic nature of many taxa. We used biodiversity information derived from high-throughput sequencing (HTS) to elucidate the relationship between soil properties and invertebrate biodiversity in the Prince Charles Mountains, East Antarctica. Across 136 analysed soil samples collected from Mount Menzies, Mawson Escarpment and Lake Terrasovoje, we found invertebrate distribution in the Prince Charles Mountains significantly influenced by soil salinity and/or sulfur content. Phyla Tardigrada and Arachnida occurred predominantly in low-salinity substrates with abundant nutrients, whereas Bdelloidea (Rotifera) and Chromadorea (Nematoda) were more common in highly saline substrates. A significant correlation between invertebrate occurrence, soil salinity and time since deglaciation indicates that terrain age indirectly influences Antarctic terrestrial biodiversity, with more recently deglaciated areas supporting greater diversity. Our study demonstrates the value of HTS metabarcoding to investigate environmental constraints on inconspicuous soil biodiversity across large spatial scales.